Crossroads and Alternatives of the Contemporary Left (Marginalia on the Occasion of 170 years Since The First Edition of the Communist Manifesto) - Mitrović, Ljubiša R. (Sociološki pregled, 2018)
The paper discusses the actuality of the messages from the Communist Manifesto (1848) and their dealing with the practice of the functioning of the contemporary Lef in the world.The focus of the author’s problematization is – the position and crossroads of the Lef in countries in transition. Open to criticism is the phenomenon of “Americanization” of the contemporary Lef, its accommodation, integration and instrumentalization by the agents of the global capital in the context of the modern development of societies of the periphery capitalism. A particular feld of research is devoted to the possibility of renewal of the alternative Lef, as an organon of resistance and radical power encounter of the modern working world against capitalism.In the end, the author exposes his plea on the role of science and intellectuals in the fight for an alternative direction of development of modern society in the service of humanization of social relations and human emancipation.Keywords: Communist Manifesto, modern capitalism, transition, crossroad of the Lef, alternative Lef.